2000
DOI: 10.1080/02671520050128786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Teacher Support Teams in secondary schools: supporting teachers for SEN and other needs

Abstract: Teacher Support Teams (TSTs) are a way of supporting individual teachers who request support over a teaching concern relating broadly to special educational needs. This paper reports on the development of these teams and the evaluation of their workings and impact in four secondary schools. The training and setting up process were monitored over four terms and the impact assessed at the end of this period using a case study evaluation strategy. This paper provides details from two schools, one that managed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Sadly a lack of support for teachers from the education 28 system generally (Creese, Norwich & Daniels, 2000) may prevent this from being given. Like other duties such as child protection (Webb & Vulliamy, 2001), teachers' pastoral care role appears to be understated and largely unacknowledged; teachers may have to manage both recent bereavement and current reactions to past bereavements during their working day.…”
Section: The Impact On Teachers Of Bereaved Studentsmentioning
confidence: 99%
“…Sadly a lack of support for teachers from the education 28 system generally (Creese, Norwich & Daniels, 2000) may prevent this from being given. Like other duties such as child protection (Webb & Vulliamy, 2001), teachers' pastoral care role appears to be understated and largely unacknowledged; teachers may have to manage both recent bereavement and current reactions to past bereavements during their working day.…”
Section: The Impact On Teachers Of Bereaved Studentsmentioning
confidence: 99%
“…Many teachers expressed that being aware that other members of staff had behavioural problems in their classes was reassuring and increased their confidence in themselves. This positive view on peer-support is supported by evaluations of other schemes (Creese et al, 2000;Hayes et al, 2007;Stringer et al, 1992). It is then perhaps surprising that only two out of the eight statements in the preand post-training questionnaire relating to perceived benefits of the SSS were found to be significantly different.…”
Section: Discussionmentioning
confidence: 71%
“…Certainly the problems with time and general school organisational factors have featured in evaluations of other peer-support schemes. For example, when discussing the establishment of Teacher Support Teams (TSTs) in secondary schools, Creese et al (2000) found that in three of the four schools in the study there were problems over time and external pressures. They state that "within this culture of schooling, it is often difficult for a school, struggling to respond to its major external demands, to translate a principled support for a teacher support system like TST into the commitment of time and senior management backing that is needed" (p. 321).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations